Association of contraception use and pregnancy intention with perinatal depression risk among Omani mothers—a longitudinal cohort study - Khalaf, Atika; Al Amri, Nawal; Ny, Pernilla; Mathew, Rebecca (Frontiers in Global Women's Health, 2025)
BackgroundUnplanned pregnancy is significantly associated with an increased risk of perinatal depression (antenatal and postnatal depression), emphasizing its prevalence and its potentially detrimental effects on both maternal and child health. This study aimed to investigate the association of contraception use and pregnancy intention with the risk of perinatal depression among Omani mothers.MethodsA prospective longitudinal study design was employed to investigate perinatal depression risk in mothers attending antenatal health care services in Oman. Perinatal depression risk was assessed using the Edinburgh Postpartum Depression Scale during the third trimester and postpartum visits. Multiple linear regression analyses were utilized to explore relationships between the risk of perinatal depression and pregnancy-related factors, contraception use, and sociodemographic variables.ResultsThe study involved 300 participants with a mean age of 30.8 years (SD = 5.47). The majority of participants reported planned pregnancy (74.0%), no use of contraception (66.0%), and being multiparous (72.7%). A significantly higher proportion (87.8%) of women with planned pregnancies were primiparous (p < 0.001). Besides family structure (core family, p = 0.025) and monthly income (1,000 OMR or below, p = 0.021), mothers who were pregnant for the first time (p < 0.001), and those who were primiparous (p < 0.001) did not use contraception. The regression models showed a significant association between the antenatal and postnatal depression scores (p < 0.001, 95% CI 0.401–0.603) according to the Edinburgh Postpartum Depression Scale.ConclusionsThe findings suggest that women with unplanned pregnancies warrant attention for early detection and preventive interventions, irrespective of their emotional stance. Incorporating routine mental health screening into perinatal care can facilitate early detection, and targeted interventions, contributing to improved maternal mental well-being.